Feasibility study of using unbalanced embryos as a reference to distinguish euploid carrier from noncarrier embryos by single nucleotide polymorphism array for reciprocal translocations - Li, Rong; Wang, Jing; Gu, Ailing; Xu, Yan; Guo, Jing; Pan, Jiafu; Zeng, Yanhong; Ma, Yuanlin; Zhou, Canquan; Xu, Yanwen (Prenatal diagnosis, 2021)
Objectives To study the feasibility of using unbalanced embryos as a reference in distinguishing euploid carrier and noncarrier embryos by single nucleotide polymorphism (SNP) array‐based preimplantation genetic testing (PGT) for reciprocal translocations. Methods After comprehensive chromosome screening (CCS), euploid embryos were identified as normal or carriers using a family member as a reference. Next, unbalanced embryos were used as a reference, and the results were compared with the previous ones. Karyotypes of transferred embryos were validated by prenatal diagnosis. Results Of 995 embryos from 110 couples, 288 were found to be euploid. Using a family member as a reference, 142 and 144 embryos were tested to be euploid noncarrier and carrier respectively, and the remaining 2 embryos were undetermined. When unbalanced embryos were selected as references, all the results were consistent with the previous ones. A total of 107 embryos were transferred, resulting in 66 clinical pregnancies. Karyotypes of prenatal diagnosis were all in accordance with the results of tested embryos. Conclusions SNP array‐based haplotyping is a rapid and effective way to distinguish between euploid carrier and noncarrier embryos. In case no family member is available as a reference, unbalanced embryos can be used for identification of euploid carrier and noncarrier embryos. Key Points What's already known about this topic? Some recent studies have reported several preimplantation genetic testing approaches to distinguish between euploid carrier and noncarrier embryos for reciprocal translocations. However, all these studies have a limited sample size. What does this study add? This study evaluated the feasibility of using unbalanced embryos generated by adjacent segregation modes as references in distinguishing between euploid embryos with and without reciprocal translocations by SNP array.